PROSPEK CAPITAL MARKET GAIN DI INDONESIA - Herlina; Hidayani (Program Studi Perbankan Syariah, 2022)
The article discusses and describes a bit of governance and deregulation of the capital market as a Capital Market and increasing Capital Gain. The capital market has an important role for the economy of a country because the capital market performs two functions, namely as a means for business funding or as a means for companies to obtain funds from the community of investors (investors). Funds obtained from the capital market can be used for business development, expansion, additional working capital and others. The capital market is a means for the public to invest in financial instruments such as stocks, bonds, mutual funds. The public can place their funds according to the characteristics of the benefits and risks of each instrument.Investors' interest in issuers has increased significantly by utilizing the capital market as a source of financing and investment facility for companies and investors. This activity can be seen from the increase in companies issuing shares and bonds as well as the number of capitalized funds. The increase in the number of investors is reflected in the increase in trading volume and the composite stock price index (JCI). In modern society, the capital market can be an alternative in obtaining profits by buying shares of companies listed on the capital market or going public (selling company shares in the capital market).